Asymmetric Interfacial Intermixing Associated Magnetic Coupling in LaMnO3/LaFeO3 Heterostructures - Chen, Binbin; Gauquelin, Nicolas; Green, Robert J.; Verbeeck, Johan; Rijnders, Guus; Koster, Gertjan (Frontiers in Physics, 2021)
The structural and magnetic properties of LaMnO3/LaFeO3 (LMO/LFO) heterostructures are characterized using a combination of scanning transmission electron microscopy, electron energy-loss spectroscopy, bulk magnetometry and resonant x-ray reflectivity. Unlike the relatively abrupt interface when LMO is deposited on top of LFO, the interface with reversed growth order shows significant cation intermixing of Mn3+ and Fe3+, spreading 8 unit cells across the interface. The asymmetric interfacial chemical profiles result in distinct magnetic properties. The bilayer with abrupt interface shows a single magnetic hysteresis loop with strongly enhanced coercivity, as compared to the LMO plain film. However, the bilayer with intermixed interface shows a step-like hysteresis loop, associated with the separate switching of the “clean” and intermixed LMO sublayers. Our study illustrates the key role of interfacial chemical profile in determining the functional properties of oxide heterostructures.